Clinical Variants of Rosacea in Iraqi Patients (Medico Legal Update, 2020)
Introduction: rosacea can diagnosis by presence permanent erythema of the arched sides of the face, cheeksand nose then it affect the chin as well as brow. Method: A cross sectional study design was implemented, 50child of Rosacea, were collected from outpatients of dermatology and venereology in Merjan teaching hospitaland Alhussein teaching hospital in Thi Qar, from Jan. 2018 to Jan. 2019. All patients were identified basingon the distinctive clinical features by dermatologist, and for suspicious cases biopsy was taken to confirm thediagnosis. Results: no significant association between age groups and gender of kids. Significant associationbetween gender and types, 61.1% of females and 54% of males with with Erythemato telengectetic while30% of females and 14% of males with mixed type. No significant association between gender and types ofskin P-value more than 0.05. No significant association between gender and drugs used. P-value more than0.05. Conclusion: There is significant association between female gender and Erythematotelengectetic andmix type of rosacea, while significant association between male gender and Papulopastular type of rosacea.